Legal Protection of Regional Local Potential Through Registration of Geographical Indications of Ponda Mats to Strengthen the Community Economy In Buton Regency - Salam, Safrin; Komuna, Avelyn Pingkan; Wirawan, A. Rachmat; Slamet, Agus; Sanjaya, I Made Gunawan (Universitas Muhammadiyah Tangerang, 2024)
The character of geographical indications from the provisions of international law refers to the area of the object of geographical indications. The purpose of this research is to find the characteristics of Ponda Wasampela Mats so that they have the potential to meet the criteria to be given legal protection as a geographical indication product and analyze the local government's efforts in encouraging legal protection of Ponda Wasampela Mats as geographical indication products. This research uses the type of Socio-Legal Legal Research. The legal approach taken is the legislation approach, concept approach and case approach. The results showed that the Ponda Wasampela mat has met the criteria to be submitted for registration of geographical indications, this is reflected in the aspect of reputation, namely that it has been used during the Buton Sultanate era in traditional rituals of marriage, death events, from the aspect of quality, namely the raw material of the mat (pandan leaves) used, raw materials (dyes and seawater), leaf drying techniques, shapes / motifs, weaving techniques, the level of neatness, and the quality of the resulting mats, aspects of characteristics namely Pandanus duri leaves (as raw material), dyes (as coloring materials), economic aspects namely Ponda Wasampela Mats currently have a selling price in the range of IDR. 50,000 (fifty thousand rupiah) and has been marketed both locally and nationally. While the government's efforts in order to encourage Ponda Wasampela Mats in geographical indication registration are the local government of Buton Regency needs to initiate commitment and efforts in carrying out supervision and guidance in encouraging Ponda Wasampela Mats to be submitted for Geographical Indication registration